2005
DOI: 10.1001/jama.293.7.843
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Paternally Inherited Fetal Point Mutations for β-Thalassemia Using Size-Fractionated Cell-Free DNA in Maternal Plasma

Abstract: Context Currently, fetal point mutations cannot be reliably analyzed from circulatory fetal DNA in maternal plasma, due to the predominance of maternal DNA sequences. However, analysis of circulatory fetal DNA sequences in maternal plasma have been shown to selectively enrich for fetal DNA molecules on the basis of a smaller molecular size than maternal DNA.Objective To examine the prenatal analysis of 4 common ␤-thalassemia point mutations: IVSI-1, IVSI-6, IVSI-110, and codon 39.Design, Setting, and Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
132
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(135 citation statements)
references
References 28 publications
1
132
0
2
Order By: Relevance
“…[17][18][19][20] In view of this limitation, we previously showed that the detection of the paternally inherited SNPs is feasible for the NIPD of b-thalassaemia. 22,23 SNPs can be used regardless of the mutation of the carrier couples, they provide positive detection of the paternal allele, normal or mutant, the result can be confirmed with more than one SNP and, importantly, the more SNPs used the less diagnostic risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20] In view of this limitation, we previously showed that the detection of the paternally inherited SNPs is feasible for the NIPD of b-thalassaemia. 22,23 SNPs can be used regardless of the mutation of the carrier couples, they provide positive detection of the paternal allele, normal or mutant, the result can be confirmed with more than one SNP and, importantly, the more SNPs used the less diagnostic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Allele-specific real-time PCR is one of the first approaches that have been used to exclude paternal mutations in the maternal circulation. 17 Preferential detection of fetal alleles was achieved through initial enrichment of fetal DNA, 8,18 while others enhanced the production of the mutated fetal allele by employing either peptide nucleic acid probes 19 or COLD PCR. 20 In the specific case of b-thalassaemia, MALDI-TOF mass spectrometry has been also investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allele-specific real-time polymerase chain reaction (PCR) is one of the first approaches that have been used to exclude paternal mutations in the maternal circulation (Chiu et al, 2002). Preferential detection of fetal alleles was achieved through initial enrichment of fetal DNA (Li et al, 2005;Li et al, 2009), whereas others enhanced the production of the mutated fetal allele by employing either peptide nucleic acid (PNA) probes (Galbiati et al, 2008) or COLD PCR (Galbiati et al, 2011). In the specific case of β-thalassaemia, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has also been investigated (Li et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although recent reports have indicated that it may be possible to noninvasively detect fetal aneuploidies such as Down syndrome (trisomy 21) (Lo et al, 2007) or Mendelian single gene disorders, such as the hemoglobinopathies (Ding et al, 2004;Li et al, 2005;Galbiati et al, 2008), no test has yet been implemented in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%